Towards meaningful simulation-based learning with medical students and junior physicians. (March 2014) - Keskitalo, Tuulikki; Ruokamo, Heli; Gaba, David
<x xml:space="preserve">Abstract</x> Background: This research provides an educational perspective on simulation-based medical education by implementing both the characteristics of meaningful learning and the concepts of facilitating, training, and learning processes. Aims: This study aims to evaluate, from the perspectives of both facilitators and students, the meaningfulness of five different simulation-based courses. Methods: The courses were implemented in the spring of 2010. The data were collected from facilitators (n = 9) and students (n = 25) using group interviews (one individual interview), observations, video recordings, and pre- and post-questionnaires. The research analyzes qualitative data using the qualitative content analysis method to answer the following research question: From facilitators' and students' perspectives, how does the facilitating and training in simulation-based learning environments (SBLEs) foster the meaningful learning of students? Results: It seems that simulation-based learning is, at its foundation, meaningful since it inherently supports the many characteristics of meaningful learning. However, characteristics also exist that simulation-based learning does not inherently support. In this study, the goal-oriented, self-directed, and individual training characteristics were only somewhat supported during the facilitation and training in SBLEs. Conclusions: In running these courses in the future, facilitators should concentrate on those characteristics that were only somewhat supported.